2017
DOI: 10.1080/09523987.2017.1391523
|View full text |Cite
|
Sign up to set email alerts
|

Critical digital literacies across scales and beneath the screen

Abstract: Digital technologies and education scholarship tends to focus on either individual creative design or analysis of the political economy. To better understand how ideologies travel across networks, critical digital literacies must focus on enactments beneath the screen, as the linguistic constructs known as software can enact interests across scales of activity to 'disembed' local actions and meaning. Investigations of these mobilities and disembedding effects challenge popular notions of digital technologies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Otherwise, as Lorelei (Interview 1) a participant in the Canadian study observed, 'how are people supposed to know' how automation is working? Such pedagogies should be encouraged and expanded, inviting more-thanhuman approaches to literacy, wherein the limits of human agencies are recognised (Braidotti 2013), and where algorithms, software, codes and devices are seen as actively shaping job search and other online outcomes (Golden 2017). Moreover, because literacy mediators and job seekers are intent on succeeding in job search; carefully tracing strategies and workarounds they deploy can tell us much about the trouble spots in erecruitment processes that can also be sites for policy intervention and more ethical design.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, as Lorelei (Interview 1) a participant in the Canadian study observed, 'how are people supposed to know' how automation is working? Such pedagogies should be encouraged and expanded, inviting more-thanhuman approaches to literacy, wherein the limits of human agencies are recognised (Braidotti 2013), and where algorithms, software, codes and devices are seen as actively shaping job search and other online outcomes (Golden 2017). Moreover, because literacy mediators and job seekers are intent on succeeding in job search; carefully tracing strategies and workarounds they deploy can tell us much about the trouble spots in erecruitment processes that can also be sites for policy intervention and more ethical design.…”
Section: Discussionmentioning
confidence: 99%
“…Mau 2018;Kitchin 2017;Eubanks 2018;Mejias und Couldry 2019). Wieder andere kritisieren Fehler und Ungerechtigkeiten in prädiktiver Polizeiarbeit (Kaufmann et al 2019), digitaler Politikausformung und Meinungsbildung (Treré 2016), automatisierter Kinderfürsorge (Redden et al 2020) oder eines digitalisierten Schulwesens (Williamson 2017;Golden 2017;Williamson und Hogan 2020). Auch negative Effekte der Digitalisierung für Arbeitsbedingungen und die Umwelt wurden bereits mehrfach ausgeleuchtet (Qiu 2016;Maxwell und Miller 2012;Notley 2019;Global E-Waste Monitor 2017;China Labor Watch 2018).…”
Section: Einführungunclassified
“…First, as these applications usually are hermetically sealed, operate on a turn on/turn off basis, and are characterised by a smooth design that poses few frictions, the technology itself moves into the background and critical understanding of its functionalities and possibilities for tinkering, repair, or hacking are drastically reduced (Sørensen 2009;Beck 2011;Brox 2017;Golden 2017). Therefore, these devices invite only the most basic forms of user engagement and de-emphasise creative testing, play, and re-appropriation of essentially black-boxed technologies.…”
Section: What Is To Be Done With the Digital?mentioning
confidence: 99%
“…Furthermore, the increased use of quantifiable data to assess achievements by both teachers and pupils is in need of further critical scrutiny. As Williamson (2015), Lynch (2015;, and Golden (2017) have argued, the increasing datafication of education aimed at fostering, among other things, algorithmic thinking, combined with the growing use of complex algorithms in planning and assessment, can have problematic and unintended consequences that are not yet adequately understood and, therefore, require additional critical reflection prior to implementation.…”
Section: What Is To Be Done With the Digital?mentioning
confidence: 99%